Effect of Emotional and Informational Family Support on COVID-19 Prevention Measures in Deli Serdang Regency - Eka Lestari Sitepu; R. Kintoko Rochadi; Namora Lumongga Lubis (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of emotional and informational family support on Coronavirus Disease 2019 (COVID-19) prevention measures in Deli Serdang Regency. This type of research is quantitative with a cross-sectional design. The total population in this study was 452,676 people. The sampling technique used is voluntary sampling. The number of samples is 270 respondents. The instrument in this study used a questionnaire in the form of a google form. The data obtained in this study were analyzed by bivariate. The results showed that there is a significant effect of emotional family support on COVID-19 prevention measures in Deli Serdang Regency. There is a significant effect of informational family support on COVID-19 prevention measures in Deli Serdang Regency.